PERSEPSI MAHASISWA AKUNTANSI MENGENAI ETIKA PENYUSUNAN LAPORAN KEUANGAN - Mahmud, Amir (Universitas Negeri Semarang, 2008)
One of the goals of accounting education in Indonesia is to introduce the students to the ethics and values of accounting profession. This research focused on the effectiveness of accounting curriculum in developing studentsÃ¢â¬â¢ responsibility towards the financial statementÃ¢â¬â¢s users. We find that no different perception on ethics occurs between the new accounting students and senior accounting students. These results show that there are needs to reform the accounting curriculum particularly in accounting department faculty of economics Semarang State University, to emphasize more on ethics and values of the accounting profession. Kata Kunci: persepsi, etika penyusunan laporan keuangan